Social Forestry And Poverty Alleviation In Sigi - Kurnia, Intam; Irfan, Mohammad; Ferianto, Fiki; Aldi; Fahrial, Abd Azis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2026)
Most communities living in the Forest Estate are poor. This condition is caused by limited access to forest resources. Access restriction is claimed to be a way to reduce deforestation and land degradation allegedly caused by illegal community activities. The government, through the Social Forestry (SF) Program, aims to protect the forest while providing welfare to the community. This research attempts to explore in more depth how SF contributes to the welfare of communities living in forest areas in Sigi Regency, especially in the Community Forest Scheme in the Uyu Singgani Forest Farmer Group (FFG) of Sigimpu Village, Palopo Subdistrict and the Village Forest Scheme in the Integrated Village Forest Management Institution (VFMI) of Oo Village, Kulawi Selatan Subdistrict. The method used was Qualitative with a case study approach. Data was collected through observation, survey, and in-depth interviews. The results showed that the communities in both villages were in the prosperous category. However, the contribution of the SF program to community income is actually fairly low, especially in the HKm area. This is because land tenure is not owned by group members but by people outside the village. Meanwhile, the group business that was formed has not been consistent in carrying out production activities so it has not been enough to provide economic benefits to the community.